2015
DOI: 10.1667/rr14028.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects Investigations Based on Atmospheric Radiation Model (ATMORAD) Considering GEANT4 Simulations of Extensive Air Showers and Solar Modulation Potential

Abstract: The natural radiative atmospheric environment is composed of secondary cosmic rays produced when primary cosmic rays hit the atmosphere. Understanding atmospheric radiations and their dynamics is essential for evaluating single event effects, so that radiation risks in aviation and the space environment (space weather) can be assessed. In this article, we present an atmospheric radiation model, named ATMORAD (Atmospheric Radiation), which is based on GEANT4 simulations of extensive air showers according to pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…For this technology, α-SER is the main contribution if the emission category is L.A. (Figure 5). Besides, the orders of magnitude issued from calculations are consistent with underground experiments [22], [39].…”
Section: Ser Experimental Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…For this technology, α-SER is the main contribution if the emission category is L.A. (Figure 5). Besides, the orders of magnitude issued from calculations are consistent with underground experiments [22], [39].…”
Section: Ser Experimental Resultssupporting
confidence: 82%
“…SEE cross sections were calculated thanks to MUSCA-SEP 3 . In this work, the atmospheric radiation fields (ground and avionic) were deduced by means of an atmospheric radiation model named ATMORAD [22], which is based on GEANT4 simulations of extensive Air Showers according to primary spectra which only depend on the solar modulation potential (Force-Field Approximation [31], [32]). Moreover, the solar potential is deduced from measurements issued from the neutron spectrometer operated by ONERA [33], [34] in the Pic-du-Midi (France, +2880 m above sea level) and the Concordia scientific station (Antarctica).…”
Section: B Methodology To Calculate the Atmospheric Sermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the sensitivity against SEEs of nanoscale devices is expected to increase with the integration scale, and recent studies have demonstrated the occurrence of SEEs due to protons and muons [19], [20], [21]. Thus, this section presents Soft Error Rate (SER) calculations based on MUSCA SEP 3 [13], which have been obtained by using the SEU models that have been validated above (Subsection IV-A) and atmospheric radiation fields composed by neutron, proton and muon spectra calculated by using ATMORAD [22]. This tool is based on simulations of extensive air showers, primary spectra model (force-field approximation [23]) and neutron spectrometer network [24].…”
Section: Ser Predictions By the Musca-sepmentioning
confidence: 99%
“…These works [Hubert and Cheminet, 2015;Hubert et al, 2016] demonstrate the potential of using simulations and cascade neutron measurements to monitor the solar activity and more particularly the solar events. Indeed, recent works [Hubert and Cheminet, 2015;Hubert et al, 2016] show that the atmospheric shower modeling associated to a primary cosmic ray model allows for deducing the radiation field from cascade neutron measurements (extract from neutron monitor or spectrometers). Indeed, recent works [Hubert and Cheminet, 2015;Hubert et al, 2016] show that the atmospheric shower modeling associated to a primary cosmic ray model allows for deducing the radiation field from cascade neutron measurements (extract from neutron monitor or spectrometers).…”
Section: Introductionmentioning
confidence: 97%